Strengthening constitutional democracy through constitutional adjudication institutions: a comparative study between Indonesia and Australia - Satriawan, Iwan; Mokhtar, Khairil Azmin; Islami, Muhammad Nur; Farar, Salim (Universitas Muhammadiyah Yogyakarta, 2017)
Democracy which gives power to the majority may lead to hegemony of majority which potentially threaten rights of the minority. In response to such threats some scholars have formulated a new paradigm of democracy called “constitutional democracy”. This article compares the experience of Indonesia and Australia in incorporating the principle of constitutional democracy into their Constitutions and in creating institutions that guarantee and protect constitutional rights of their citizens. This is a doctrinal research which uses comparative approach. The establishment, role and powers of constitutional adjudication institutions in realizing the goal of state in both countries are examined and assessed. The two countries adopt different model of constitutional adjudication. Indonesia follows kelsenian model as practiced in most European countries, while Australia follows the common law model which functions the high courts as constitutional adjudication institution. The study concludes that the Constitutional Court of Indonesia and the High Court in Australia are part of the realization the goal of the countries be democratic states based on the rule of law. The Courts perform their function as the guardian of the Constitution and protector the constitutional rights of citizen with varying degree of success. The constitutional adjudication in both countries also plays a role as checks and balances mechanism of other main organs in the constitutional system. The existence of the Constitutional Court in Indonesia and the High Courts in Australia has contributed to the upholding the principle of constitutional democracy and strengthening the consolidation of democracy.